2006
DOI: 10.1542/peds.2005-2493
|View full text |Cite
|
Sign up to set email alerts
|

Disposable Colorimetric Carbon Dioxide Detector Use as an Indicator of a Patent Airway During Noninvasive Mask Ventilation

Abstract: Colorimetric carbon dioxide detectors are useful indicators of proper endotracheal tube placement. We have found that they also are helpful during bag and mask ventilation as an indicator of a patent airway. In this report, we describe our experience with these devices for use during preintubation airway stabilization as observed during videotaped performances from a prospective, randomized trial of intubation premedication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(35 citation statements)
references
References 9 publications
1
29
0
5
Order By: Relevance
“…55,56 However, it is unclear whether the use of CO 2 detectors during mask ventilation confers additional benefit above clinical assessment alone (Class IIb, LOE C).…”
Section: Initial Breaths and Assisted Ventilationmentioning
confidence: 99%
“…55,56 However, it is unclear whether the use of CO 2 detectors during mask ventilation confers additional benefit above clinical assessment alone (Class IIb, LOE C).…”
Section: Initial Breaths and Assisted Ventilationmentioning
confidence: 99%
“…55 We have found that over 80% of such infants receiving bag and mask breaths have evidence of airway obstruction during the initial breaths and that such airway obstruction may persist for 37 or more breaths over a period of a minute or longer. 56 These obstructed breaths may often go unrecognized in the absence of a CO 2 detection device and may lead to bradycardia and hypoxia, and, in time, to further, more aggressive and hazardous procedures, such as increased pressure compressions, intubation or medications, if not rapidly recognized and relieved.…”
Section: Bag and Mask Ventilationmentioning
confidence: 92%
“…The use of colorimetric exhaled CO 2 detectors during face mask ventilation of small numbers of preterm infants in the intensive care unit (LOE 4 72 ) and the delivery room (LOE 4 73 ) has been reported and may help identify airway obstruction. It is unclear whether the use of exhaled CO 2 detectors during face mask ventilation confers additional benefit over clinical assessment alone.…”
Section: Consensus On Sciencementioning
confidence: 99%